HPV vaccine development after more than ten years approval - Brahmana Askandar (Universitas Airlangga, 2020)
At present, ten years have passed since the human papillomavirus (HPV) vaccine was first approved for use in humans. Research related to HPV vaccine, both in terms of effectiveness and immugenicity in its development, has been widely carried out, such as in terms of the indications of the HPV vaccine use that is not only for preventing cervical cancer, the guidelines for administering 2-dose HPV vaccines for those under 15 years of age, and the discovery of the latest HPV vaccine types: nonavalent HPV vaccine. This review literature discusses all aspects of the development of HPV vaccine since it was first approved for use in humans in 2006.